Potential for the use of pluvial water for potable purposes in the University of the State of Pará (Research, Society and Development, 2021)
Rainwater harvesting is a viable way to optimize the use of water resources and encourage sustainable development. The purpose of this article is to determine the water saving potential in Block I of the University of the State of Pará (UEPA). For this, the study was carried out with the application of Neptune, a computer software for the analysis of rainwater that grants the potential of saving water for less noble purposes for each volume of reservoir. Daily rainfall data over a period of 31 years (1987-2017) were considered, as well as a catchment area of ​​543.55 m², number of users and water demands for non-noble and rainy purposes. The total water demand was 30L / student.day; rainwater demands were taken as a percentage of water demand for less noble purposes, 40% and 100% were considered. The results indicated water saving potentials for less noble purposes of 23.21% and 33.19%, and ideal reservoir volumes of 19,250L and 18,750L. The State University of Pará-Marabá / PA has a favorable potential for using rainwater as a way of saving water supplied by the University's supply system, due to the high rainfall and large catchment areas, however, the dimensioning of the tank rainwater storage must be carried out in accordance with each specific situation, in order to assess the feasibility of the project.